2006
DOI: 10.1007/bf02743146
|View full text |Cite
|
Sign up to set email alerts
|

How primary care providers talk to patients about alcohol a qualitative study

Abstract: Findings from this single site study suggest that provider discomfort and avoidance are important barriers to evidence-based brief alcohol counseling. Further investigation into current alcohol counseling practices is needed to determine whether these patterns extend to other primary care settings, and to inform future educational efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 44 publications
5
101
1
2
Order By: Relevance
“…In a study about physician alcohol screening practices, Sharp and Vacha-Haase (2010) noted physician alcohol screening practices and indicated that physicians reported screening 73% of their new patients upon intake and only 44% of their existing patients. Despite the lack of conversations about alcohol, research has suggested that conversations and brief alcohol counseling during primary care appointments reduce alcohol consumption, adverse health consequences, and health care utilization in patients who drink above recommended limits (Bertholet, Daeppen, Wielishbach et al, 2005;McCormick, Cochran, Back et al, 2006;Moyer, Finney, Wearingen et al, 2002). Regardless of the positive health benefits, patient-doctor conversations about alcohol use remain sparse due to the topic's sensitive nature.…”
Section: Chapter 5: Discussionmentioning
confidence: 99%
“…In a study about physician alcohol screening practices, Sharp and Vacha-Haase (2010) noted physician alcohol screening practices and indicated that physicians reported screening 73% of their new patients upon intake and only 44% of their existing patients. Despite the lack of conversations about alcohol, research has suggested that conversations and brief alcohol counseling during primary care appointments reduce alcohol consumption, adverse health consequences, and health care utilization in patients who drink above recommended limits (Bertholet, Daeppen, Wielishbach et al, 2005;McCormick, Cochran, Back et al, 2006;Moyer, Finney, Wearingen et al, 2002). Regardless of the positive health benefits, patient-doctor conversations about alcohol use remain sparse due to the topic's sensitive nature.…”
Section: Chapter 5: Discussionmentioning
confidence: 99%
“…35 These challenges, in addition to ambiguous guidelines and research findings about HCVand alcohol consumption, 6,7 little formal training about HCV, and caring for fewer symptomatic HCV patients than GI providers, may lay the groundwork for ambiguous alcohol recommendations to HCV patients seen in IM clinics. In addition, studies on advice about alcohol consumption in IM settings have focused only on "at-risk" or "heavy drinkers" 36 those "screening positive for alcohol misuse" 37,38 and those who have undergone alcohol treatment recently. 39 HCV is a major public health issue with just over four million Americans currently infected, 40 and projected medical costs for the years 2010 to 2019 of almost $11 billion, and societal costs of $54 billion due to years of life lost under the age of 65.…”
Section: Discussionmentioning
confidence: 99%
“…A study in non-HIV patients of audio-recorded conversations between 47 patients with problematic alcohol use and their providers found that providers seemed uncomfortable when talking about alcohol, engaged in little follow-up to disclosures, and tended to give tentative advice. 22 Similarly, a study in New Zealand that analyzed the dialogue between 171 patients and their providers found that discussion of alcohol or drugs (including tobacco) occurred in less than 25 % of visits. 20 Neither of these studies assessed how clinicians ask about substance use.…”
Section: Introductionmentioning
confidence: 99%